Implementation of Work Sharing Technique to Improve Line Efficiency in Sewing Section: A Case Study - Islam, Marzia; Sultana, Mst. Farzana; Chowdhury, Md. Shafiqul Islam; Mridha, Jaglul Hoque; Sarker, Taposh Ranjan (European Scientific Journal, ESJ, 2019)
This paper focuses on analyzing the garment processes and operation bulletin for a particular sewing line in Mahadi Fashion (PVT) Limited. The production rate of the existing layout was not close to the target. The target was 175 pieces per hour but actual production was 138 pieces per hour. So we analyzed the layout and found out the bottleneck area. Then we rearranged the workload by work sharing and reduced manpower. By doing so, actual production was 160 pieces per hour, which is near to the target, and line efficiency increased to 77%, where the existing sewing line layout was 55%. After reducing the bottleneck in sewing line capacity, we achieved 160 pieces per hour against the 138 pieces in the existing layout.